The Effect of Ergonomic Exercise on Reducing Blood Pressure in Hypertensive Elderly at Ciparay Panti Sosial Tresna Werdha Ciparay - Irawan, Erna; Maidartati, Maidartati (Jurnal Pendidikan Keperawatan Indonesia, 2023)
Hypertension is a condition when blood pressure is at 140/90 mmHg or more. Every year people with hypertension continue increased, it is estimated that in 2025 as many as 1.5 billion people suffer from hypertension... One way to reduce blood pressure is to do ergonomic exercises. The purpose of this study is to find out ergonomic exercises for decreasing blood pressure on elderly hypertension at Ciparay Elderly Social Rehabilitation Institution. This research used quasi Experiment design by designing a pre and post test group. The population of this study was hypertensive elderly totaling 70 people, The sampling technique uses non probability sampling with the technique purposive sampling, its about 23 respondent. Data collection using questionnaires, observation sheets, and digital sphygmomanometer. The number of respondents was 23 respondents, ergonomic exercises done 3 times repeatedly - according to 3 weeks. Pressure measurement blood is done before gymnastics (pre test) and after 30 minutes after gymnastics (post test). Statistical test results show the average systole pressure before gymnastics is equaldari to160.15 mmHg to and the remaining gymnastics 140.05 mmHg, a decrease of 20.1 mmHg. Diastolic pressure before gymnastics isfrom 96.28 mmHg and as is gymnastics to 86.11 mmHg, a decrease of 10.17 mmHg. Data analysis using Paired Sample T-Test related to ergonomic exercises for impairment blood pressure in hypertensive elderly with systole pressure p value = 0,000 and diastolic pressure p = 0,000.The conclusion Can be accessed the effect of ergonomic exercises on reducing blood pressure in elderly hypertension. The results of ergonomic exercise intervention can be used as a therapy in pressure reduction blood and it is expected that the elderly are routinely approved for ergonomic exercises.